2021
DOI: 10.3991/ijim.v15i09.19993
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Devices Applied in Self-Studying English as a Foreign Language Among Non-Native Students in Vietnam and Japan

Abstract: <p class="Affiliation"><strong>Abstract – </strong>In the era of technology, learning can be supported with mobile devices inside and outside of the classroom. In the hope of taking advantage of technology advances, teachers worldwide have integrated technologies into teaching to effectively deliver lesson content and address students’ needs. However, few non-native learners are exposed to mobile devices to optimize self-studying English outside the classroom. Thus, the present paper conducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Even though [1] reported no significant difference between the experimental and control groups on the post-test, but he found that students attitudes towards the use of mobile applications in teaching vocabulary is positive. [17] also inform in their research that mobile learning benefits led to strong and positive preferences for using mobile devices to self-study English.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though [1] reported no significant difference between the experimental and control groups on the post-test, but he found that students attitudes towards the use of mobile applications in teaching vocabulary is positive. [17] also inform in their research that mobile learning benefits led to strong and positive preferences for using mobile devices to self-study English.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have studied the pedagogical possibilities of mobile phones for basic English language learning and vocabulary learning. The findings either shows a significant improvement because of using the MALL ( [2], [12], [15]) or just positively shows user preference towards using it for learning ( [16], [17], [19]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of e-Learning indeed allows the learning process to be carried out anytime and anywhere. However, with m-Learning, students or teachers can use the cell phone feature to get a better user experience [11]. With m-learning, students can complete learning activities more quickly than with desktop or laptop computers.…”
Section: M-learningmentioning
confidence: 99%
“…Learning EFL and ICT are fundamental for learners majoring computer science and control engineering not only for the use in academic fields but also for the means of communication worldwide. Students are expected to develop themselves through ICT competence and computing literacies [3,4]. With the assistance of information technology, learners are provided with challenges and opportunities to optimize knowledge and skills through online learning [5].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies revealing the positive impacts of integrating technology into teaching and learning on the students' achievement [6,7,8]. With mobile devices, such as smartphones, tablets or computers, students were able to enhance their outcomes if mobile devices are integrated to the learning process frequently [4].…”
Section: Introductionmentioning
confidence: 99%